Long-Term Follow-Up in Children with Anisocoria: Cocaine Test Results and Patient Outcome - Fabienne C. Fierz; Christina Gerth-Kahlert (Journal of Ophthalmology)
Background. Evaluation of anisocoria including pharmacological testing for Horner’s syndrome in the pediatric population is challenging in view of potential serious underlying disease. We describe cocaine test results, outcome of systemic investigation, and long-term follow-up in children with anisocoria. Methods. Retrospective review of medical records and phone interview of consecutive pediatric patients (<18 years old) who underwent cocaine testing from August 2007 to July 2015 at a tertiary referral centre. Results. A total of 35 patients were included with a positive, negative, or inconclusive cocaine test in 12/35, 19/35, and 4/35, respectively. Systemic investigation was performed in 11 of the patients with a positive and in 2 of the patients with an inconclusive cocaine test result. Mediastinal Hodgkin lymphoma was found in one patient with an inconclusive cocaine test result. Two other cases were presumably related to birth trauma and surgical trauma. None of the other children further developed any pathology during the follow-up period of 34.8 months (range 0–106.6). Conclusions. In most children with anisocoria and a positive cocaine test result, systemic investigation did not reveal any underlying etiology. The only malignant disease was diagnosed in a patient with a suspicion of Horner’s syndrome but with an inconclusive cocaine test result in our cohort.